Receptivity towards code-switching in Malay television series - Ting, Su Hie; Ooi, Kien Bee (2013)
The study examined receptivity of 71 university students towards use of code-switching in Malay television drama series. A short clip from a Malay television series with code-switching from Bahasa Malaysia t oEnglish was played before students filled in a questionnaire. Code-switching Is mostly viewed negatively but 94% of the students reported that they often code-switching in their daily interactions with friends and lecturers. The non-Malay students were more inclined to feel that code-switching corrupts the languages and prevents them from mastering the languages but they were similar to the Malay students in their views on negative attribution of image, identity and patriotism. However, a small proportion of the students felt that those who code-switch are seen as educated, sophisticated and racially torelant.